투자자관심과 시장상황이 한국주식시장의 모멘텀 효과에 미치는 영향 - 엄철준(Cheoljun Eom); 장욱(Uk Chang); 강병진(Byung Jin Kang); 이우백(Woo Baik Lee); 박종원(Jong Won Park) (한국증권학회지, 2020)
본 연구는 우리 시장에서 투자자관심과 시장상황이 모멘텀 효과에 미치는 영향을 분석하였다. 분석결과, 투자자관심이 높은 주식집단(높은 회전율 집단)에서 유의한 음(-)의 모멘텀 이익이 확인되나, 투자자관심이 낮은 주식집단(낮은 회전율 집단)에서는 유의한 결과를 얻을 수 없다. 높은 회전율 집단에서패자포트폴리오는 미래기간에 큰 폭의 가격반전으로 유의한 양(+)의 성과를 실현한다. 둘째, 과잉반응정도는 모멘텀 효과에 의미있는 영향을 미친다. 회전율이 높은 집단에서 과잉반응 정도가 높은 집단이낮은 집단에 비해 보다 강한 음(-)의 모멘텀 이익을 보여준다. 셋째, 음(-)의 모멘텀 이익은 시장상황의동적 특성에 관계없이 관찰되나, 시장상황이 반전하는 전환시장에서 보다 강한 음(-)의 모멘텀 이익을보여준다. 넷째, 높은 회전율 집단에서 보이는 음(-)의 모멘텀 이익은 공통요인의 영향을 통제한 후에도유의하게 나타나며, 개별주식의 변동성이나 유동성 특성과 관계없이 나타난다. This study examines the effects of investor attention on momentum in the Korean stock market. The results reveal significant negative momentum profits in stock groups with high investor attention (high turnover stocks), but insignificant results in those with low investor attention (low turnover stocks). Within high turnover stock groups, the winner portfolio has a declining price trend and insignificant performance, while the loser portfolio realizes significant positive performance through a substantial price increase in the future period. The momentum effect is highly dependent on the reversed performance of the loser portfolio. Second, the performance of the large overreaction stock group shows a more significant negative momentum effect compared to the low overreaction stock group, that is, the degree of overreaction significantly affects the momentum effect. Third, negative momentum profits are consistently observed regardless of the market dynamics. Specifically, more substantial and significant negative performance occurs in the transition market, where the market situation reverses between the past and future periods. Fourth, negative momentum profits are consistently identified even after controlling for the impact of common factors and volatility and liquidity into turnover. Our findings are qualitatively different from the characteristics of the traditional momentum effects generally reported in Western countries. KCI Citation Count: 0